Ultrastructure of sheep primordial follicles cultured in the presence of indol acetic acid, EGF, and FSH - Andrade, Evelyn Rabelo; Maddox-Hyttel, Poul; Landim-Alvarenga, Fernanda Da Cruz [UNESP]; Viana Silva, José Roberto; Alfieri, Amauri Alcindo; Seneda, Marcelo Marcondes; Figueiredo, José Ricardo; Toniolli, Ricardo (Hindawi, 2011)
The aim of this study was to investigate the ultrastructural characteristics of primordial follicles after culturing of sheep ovarian cortical slices in the presence of indol acetic acid (IAA), Epidermal Growth Factor (EGF), and FSH. To evaluate ultrastructure of primordial follicles cultured in MEM (control) or in MEM containing IAA, EGF, and FSH, fragments of cultured tissue were processes for transmission electron microscopy. Except in the control, primordial follicles cultured in supplemented media for 6d were ultrastructurally normal. They had oocyte with intact nucleus and the cytoplasm contained heterogeneous-sized lipid droplets and numerous round or elongated mitochondria with intact parallel cristae were observed. Rough endoplasmic reticulum (RER) was rarely found. The granulosa cells cytoplasm contained a great number of mitochondria and abundant RER. In conclusion, the presence of IAA, EGF, and FSH helped to maintain ultrastructural integrity of sheep primordial follicles cultured in vitro. © 2011 Evelyn Rabelo Andrade et al.
Keywords: Ovis aries